Оптимізація системи автоматичного керування подачею живильного розчину в теплицях - Синявський, О. Ю.; Савченко, В. В. (Energy and Automation, 2017)
OPTIMIZATION OF THE AUTOMATIC CONTROL SYSTEM FOR  nutrient solution supply IN THE GREENHOUSEA. Sinyavsky, V.  Savchenko In greenhouses, watering plants is fed with a nutrient solution through an automatic drip irrigation system. Watering of plants is often carried out according to the given agronomic program depending on the intensity of solar radiation. When applying the system of drip irrigation, the loss of mineral fertilizers and water is not less than 25 %.The purpose of the study is to optimize the system of automatic control of the moisture content of mineral wool.The automatic humidity control system of mineral wool works in automatic mode - according to the signals of the primary humidity converter of the substrate, which enter the regulator, which controls the actuators, and according to the time program from the watering machine.To measure the humidity of the substrate, the UHF-moisture of the mineral wool of the IMESG design was selected. The executive mechanism is a pump with an electromagnetic valve.Since for the object of control of the ratio τ/T